Mid wall fibrosis on CMR with late gadolinium enhancement may predict prognosis for LVAD and transplantation risk in patients with newly diagnosed dilated cardiomyopathy—preliminary observations from a high‐volume transplant centre. (29th July 2015) - Venero, Jose V.; Doyle, Mark; Shah, Moneal; Rathi, Vikas K.; Yamrozik, June A.; Williams, Ronald B.; Vido, Diane A.; Rayarao, Geetha; Benza, Raymond; Murali, Srinivas; Glass, Jerry; Olson, Peter; et al.
Abstract: Background: Patients with newly diagnosed dilated cardiomyopathy (DCM) and advanced heart failure have a very high morbidity and mortality with an unpredictable clinical course. We investigated the role of cardiovascular magnetic resonance (CMR) imaging using late gadolinium enhancement (LGE) in this cohort of high‐risk patients. We hypothesized that LGE has high prognostic value in primary DCM patients referred for possible transplantation/left ventricular assist device (LVAD) consideration. Methods: Over 49 consecutive months, 61 consecutives DCM patients were referred for standard CMR(1.5T, GE) to interrogate the LV pattern, distribution, and extent of LGE (MultiHance, Princeton, NJ). Inclusion criteria for a primary non‐ischaemic DCM and EF <45% were met in 31 patients. DCM patients were categorized into: (i) presence of midwall LV stripe (+Stripe) and (ii) absence of midwall stripe (−Stripe) groups. Primary outcome was defined by the composite of death, need for LV assist device (LVAD), and urgent orthotopic cardiac transplantation (Tx) during a 12‐month follow‐up period. Kaplan–Meier survival analysis was conducted grouping patients by +Stripe and −Stripe. Results: There were no differences between groups for demographics, blood pressure, labs, baseline LVEF, NYHA class, or invasive haemodynamics. There were 18 patients (58%) with +Stripe. Nine events occurred: seven patients required urgent Tx and/or LVAD implantation and two patients died. The +Stripe categorization strongly predicted the need for LVAD, urgent Tx surgery, and death (log‐rank = 9, P = 0.002). All the events occurred in the +Stripe patients with no MACE experienced in the −Stripe group. The −Stripe group experienced marked signs of improvement in LVEF ( P = 0.01) at follow‐up. LVEDD was predictive of need for LVAD/Tx and death by univariate analysis. Otherwise, no common clinical metric such as LVEF, LVEDV, RVEF, RVEDV, or any invasive haemodynamic parameter predicted MACE. Conclusions: The presence of +Stripe on CMR is strongly predictive of LVAD, transplant need, and death during a 12‐month follow‐up period in DCM patients in this proof of concept study. All −Stripe patients survived without experiencing any events. Incorporating CMR imaging into routine clinical practice may have prognostic value in DCM patients; indicating conservative management in low‐risk patients while expectantly managing high‐risk patients.